Effects of Obesity and Diabetes on Oxidized Low Density Lipoproteins and CD36 Membrane Receptor (FS18-06-19). (13th June 2019) - Hajri, Tahar; Talishinskiy, Toghrul; Thomas, Tina; Jenkins, Megan; Amianda, Erica; Wong, Sarah; Ewing, Douglas; Eid, Sebastian; Schmidt, Hans
Abstract: Objectives: Clustering differentiating 36 (CD36), a scavenger receptor highly expressed in macrophages and monocytes, is implicated in the early stages of atherosclerosis due to its ability to internalize oxidized low density lipoprotein (oxLDL). Although obesity is a major risk for diabetes, some obese subjects seem to be more resistant to the development of metabolic and pathological disturbances. This study was designed to compare the concentration of circulating oxLDL and the expression of monocyte CD36 in obese diabetic (OD) and obese non-diabetic (OND) subjects, and tested whether bariatric surgery exerts similar effects in both groups Methods: Blood was collected prospectively from OD and OND subjects ( n  = 21 per group) before Roux-en-Y-gastric bypass (RYGB) and 12 months postoperatively. Plasma glucose and lipoproteins were measured enzymatically. Iinsulin and glycosylated hemoglobin A1c (GHbA1c) were analyzed by enzyme-linked immunosorbent (Elisa). Insulin resistance index (HOMA-IR) was calculated. The expression of monocytes CD36 was assayed by western blot and RT-PCR. Results: Although OD and OND subjects had comparable body mass index Pre-RYGB (43 ± 9 vs 41 ± 8 kg/m 2, respectively), blood insulin, HbA1c and HOMA-IR were significantly higher in OD (29 ± 5 μU/mL, 7.8 ± 0.8% and 9.8 ± 2.5, respectively) than OND subjects (19 ± 4 μU/mL, 5.7 ± 0.5% and 5.9 ± 1.4, respectively). In addition, the level of plasma oxLDL (49.2 ± 11.9 vs 31.4 + 9.5 mU/ml) was greater in OD than OND subjects. Moreover, the expression of monocyte CD36 (protein level and mRNA abundance) was significantly higher in OD than OND subjects. The effect of RYGB was beneficial in both OD and OND subjects. At 12 months post-RYGB, there were comparable reduction of BMI in OD and OND subjects. Plasma levels of insulin, HbA1c and HOMA-IR also declined in both groups, but the effect was stronger in OD subjects, leading to comparable final values between groups. Plasma oxLDL and monocyte CD36 expression were also reduced in both groups and were comparable at 12 months post-RYGB. Conclusions: These results show that obese diabetic subjects exhibit high levels of oxLDL and monocyte CD36, both of which could increase the risk of cardiovascular diseases. RYGB-induced weight loss could be beneficial for both obese and obese diabetic subjects. Funding Sources: Hackensack University Medical Center.